Autobiography report in the context of solidarity economy and mental health: a way of flying? Experience in the context of solidarity economy and mental health: a way of flying? - Smaniotto Roschel Rotger, Íris (Brazilian Journal of Mental Health, 2024)
Overcoming report. The author, who has passed through a psychic suffering, wrote this report aiming to discuss the effectiveness of assemblies in solidarity economy enterprising, based on her own reports and subjective perceptions, related to the mental health users’ silence. Through the words, art and desire of the group and her own changing, she shares her experiences pointing to the factors and agents (actors) who favored her conquers in the subjective and practical senses. After years of silencing, she manifests her voice, being listened and respected, through the democratic processes of solidarity economy that exists within the psychosocial rehabilitation, believing in the fact that self-management is one of the key factors of her recovering. After observing the solidary economy assemblies, doubts about the effectiveness of these actions have appeared. The author claims for the singularity of each worker of the solidary economy enterprising and observes the distancing existent between theory and practice. Everything appears in her longings to answer her questionings through the method of oral history for promoting concrete changes and benefit those who pass or passed through the same processes of psychic suffering.